2011
DOI: 10.1111/j.2044-8325.2011.02020.x
|View full text |Cite
|
Sign up to set email alerts
|

Leading organizational change in the ‘new’ South Africa

Abstract: This paper reports on a two-pronged qualitative research study that used leaders' life stories and the case research method to understand the leadership of change in 14 South African organizations. We describe how leaders led the changes required to balance the imperatives emanating from South Africa's socio-political changes and return the country to the international business arena, as well as the challenges created by years of inequality and neglect of the socio-economic development of the majority of its p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 51 publications
0
28
0
Order By: Relevance
“…Given that these ideas are at present exploratory and incipient the interconnecting lines between the variables are dashed lines. The organisational, managerial and administrative life in African organisations has been shown to be rather nuanced with many interplaying variables, often emanating from national political issues (Munene, 1995;Nkomo and Kriek, 2011).…”
Section: Conceptual Framework For Investigating Research Culturementioning
confidence: 99%
“…Given that these ideas are at present exploratory and incipient the interconnecting lines between the variables are dashed lines. The organisational, managerial and administrative life in African organisations has been shown to be rather nuanced with many interplaying variables, often emanating from national political issues (Munene, 1995;Nkomo and Kriek, 2011).…”
Section: Conceptual Framework For Investigating Research Culturementioning
confidence: 99%
“…One review of seventeen papers dealing with management in Africa (Lituchy, Punnett, Ford, & Jonsson, 2009) found that three dealt with Africa in general, another with Southern Africa, and the other with Western Africa. More recently, there have been studies on absenteeism (Addae, Johns, & Boies, 2013), and organizational change (Nkomo & Kriek, 2011) based in African countries. The continent of Africa consists of about 55 countries (the actual number depends on whether places such as Somaliland are included as countries), and the studies identified addressed only five of these countries, with South Africa dominating.…”
Section: Filling the Gap In Business And Management Researchmentioning
confidence: 99%
“…The continent of Africa consists of about 55 countries (the actual number depends on whether places such as Somaliland are included as countries), and the studies identified addressed only five of these countries, with South Africa dominating. More recently, there have been studies on absenteeism (Addae, Johns, & Boies, 2013), and organizational change (Nkomo & Kriek, 2011) based in African countries. Furthermore, we did not find any management studies specifically addressing the African Diaspora.…”
Section: Filling the Gap In Business And Management Researchmentioning
confidence: 99%
“…(p. 343) and is at the heart of our quest for a localized and contextualized understanding of the meaning of leadership in Africa Despite a growing body of scholarship in the area of leadership in Africa, the literature remains small in comparison to the wealth of research and applications available elsewhere in the general area of leadership. Writings within the last ten years by scholars such as Jackson (2004); Puplampu (2005Puplampu ( , 2010; Nkomo and Cook (2006); Jackson, Amaeshi, and Yavuz (2008); Walumbwa, Avolio, and Aryee (2011); Muchiri (2011); Nkomo and Kriek (2011), and Lituchy, Ford, and Punnett (2013) demonstrate a number of issues. Cumulatively, these scholarly outputs show that: (a) there is significant impact of leadership action and/or inaction on the profitability of African organizations and nations; (b) there is growing interest in leadership and management issues in and on Africa; (c) there is limited availability of relevant scholarly material, requiring continuous and consistent effort on the part of researchers, and (d) there is still more to learn in order to fully understand the interplay between culture, tradition, history, and personal dispositions in how the leadership process and leaders operate in Africa.…”
Section: Résumémentioning
confidence: 99%
“…As Muchiri (2011) noted, some of the emerging literatures show that concepts such as authentic leadership and servant leadership may help elucidate the causal links between leaders' behaviours and organizational outcomes; however, an Africa context and philosophy remain insufficiently explored. Nkomo and Kriek (2011), in a study of corporate leadership through times of major change, showed conclusively that sociopolitical histories and socioeconomic contexts-at the level of the nation state-are important milieus that corporate leaders in Africa navigate on a daily basis. The extant Western literatures and examples hardly draw on such nuances in their discourses on leadership.…”
Section: Résumémentioning
confidence: 99%